+0  
 
+4
163
3
avatar+176 

Suppose \(\frac{1}{x^3-x^2-21x+45}=\frac{A}{x+5}+\frac{B}{x-3} + \frac{C}{(x - 3)^2}\)
where A, B, and C are real constants. What is A?

 Jul 2, 2020
 #1
avatar+21958 
+4

x3 - x2 - 21x + 45  can be factored into  (x + 5)(x -3)2

so multiply each term by   (x + 5)(x -3)2 

You'll end with:      1  =  A(x - 3)2 + B(x - 3)(x + 5) + C(x + 5)

                              1  =  A(x2 - 6x + 9) + B(x2 + 2x - 15) + C(x - 5)

                              1  =  Ax2 - 6Ax + 9A + Bx2 + 2Bx - 15B + Cx - 5C

             0x2 + 0x + 1  =  Ax2 + Bx2  - 6Ax + 2Bx + Cx + 9A - 15B - 5C

 

So:            Ax2 + Bx2  =  0x2   --->   (A + B)x2  =  0x2   --->    A + B  =  0

       -6Ax + 2Bx + Cx  =  0x     --->   (-6A + 2B + C)x  =  0x   --->   -6A + 2B + C  =  0

           9A - 15B - 5C  =  1   

 

Now, solve these three equations simultaneously:         A +     B          =  0

                                                                                     -6A +   2B +  C  =  0

                                                                                       9A - 15B - 5C   =  1   

 Jul 2, 2020
 #2
avatar+176 
+1

um i dont understand but thankyou

BillyBobJoeJr  Jul 3, 2020
edited by BillyBobJoeJr  Jul 3, 2020
 #3
avatar+21958 
+2

To finish:

 

First, eliminate C from the last two equations:

 

-6A + 2B + C  =  0     --->   x 5   --->   -30A + 10B + 5C  =  0

9A - 15B - 5C  =  1   --->                        9A - 15B  - 5C  =  1

(add down)                                          -11A  - 5B            =  1

 

Combining this result with the first equation:

     A +  B  =  0   --->   x 11   --->   11A + 11B  =  0

-11A - 5B  =  1   --->                    -11A  -   5B  =  1

(add down)                                               6B  =  1   --->   B = 1/6

 

A + B  =  0   ---->   A + (1/6)  =  0   --->   A  =  -1/6

 

-6A + 2B + C  =  0   --->   -6(-1/6) + 2(1/6) + C  =  0   --->   1 + 1/3 + C  =  0   --->   C  =  -4/3

 Jul 6, 2020

12 Online Users